The Encyclopedia of Applied Linguistics 2012
DOI: 10.1002/9781405198431.wbeal0728
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Heritage Language Maintenance

Abstract: Heritage language (HL) maintenance refers to the preservation of an immigrant (e.g., Japanese, Chinese, Hebrew, Russian), an indigenous (e.g., Cherokee, Zuni, Chumash), or a colonial (e.g., Spanish, French, or German from earlier settlers in North America) language (Fishman, 2001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Consequently, among children in immigrant families, literacy education in a heritage language holds significant value in cultivating a deeper understanding of and positive attitude toward their language and culture. Previous research has shown that children with strong literacy skills in their heritage language are more likely to maintain their proficiency in spoken language, and literacy education contributes to the preservation and growth of the heritage language (Chevalier, 2004;Lee, 2012;Leonard et al, 2020). Exploring the factors that influence literacy skills in a heritage language and their relationship with child-external factors is critical to enhancing those skills among children in immigrant families.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, among children in immigrant families, literacy education in a heritage language holds significant value in cultivating a deeper understanding of and positive attitude toward their language and culture. Previous research has shown that children with strong literacy skills in their heritage language are more likely to maintain their proficiency in spoken language, and literacy education contributes to the preservation and growth of the heritage language (Chevalier, 2004;Lee, 2012;Leonard et al, 2020). Exploring the factors that influence literacy skills in a heritage language and their relationship with child-external factors is critical to enhancing those skills among children in immigrant families.…”
Section: Introductionmentioning
confidence: 99%